2014
DOI: 10.1097/md.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe Chlorite Poisoning Successfully Treated With Early Administration of Methylene Blue, Renal Replacement Therapy, and Red Blood Cell Transfusion

Abstract: The case of a 55-year-old man who attempted suicide by ingesting <100 mL of 28% sodium chlorite solution is presented. On arrival in the intensive care unit, the patient appeared cyanotic with lowered consciousness and displayed anuria and chocolate brown serum.Initial laboratory tests revealed 40% of methemoglobin. The formation of methemoglobin was effectively treated with methylene blue (10% after 29 hours).To remove the toxin, and because of the anuric acute renal failure, the patient received renal replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“… Unproven chemical Efficacy Safety Toxicology profile References Chlorine dioxide solution (CDS) NEE a NEE a Nausea, vomiting, diarrhea, severe dehydration, anuria, unconsciousness, cyanosis and chocolate brown serum. 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 Miracle Mineral solution (MMS) NEE a NEE a Nausea, vomiting, diarrhea, severe dehydration, fever, chills or rigors, tachycardia, and dry cough 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 Colloidal silver NEE a NEE a Argyria or jaundice, dehydration, fever, confusion, hypotension, hypoxia, lethargy, slurred speech, organ damage, profound disfiguration, hypochloremia, hyponatremia, cell apoptosis or necrosis, oxidative stress, and cholelithiasis 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , …”
Section: Unproven Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“… Unproven chemical Efficacy Safety Toxicology profile References Chlorine dioxide solution (CDS) NEE a NEE a Nausea, vomiting, diarrhea, severe dehydration, anuria, unconsciousness, cyanosis and chocolate brown serum. 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 Miracle Mineral solution (MMS) NEE a NEE a Nausea, vomiting, diarrhea, severe dehydration, fever, chills or rigors, tachycardia, and dry cough 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 Colloidal silver NEE a NEE a Argyria or jaundice, dehydration, fever, confusion, hypotension, hypoxia, lethargy, slurred speech, organ damage, profound disfiguration, hypochloremia, hyponatremia, cell apoptosis or necrosis, oxidative stress, and cholelithiasis 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , …”
Section: Unproven Chemicalsmentioning
confidence: 99%
“…195 , 196 , 197 There is a case report of life-threatening complications from poisoning with sodium chlorite, where a 55-year-old man arrived to the ICU in a cyanotic state with lowered consciousness displaying anuria and chocolate brown serum. 200 The patient required renal replacement therapy, treatment with methylene blue, and red blood cells transfusion. 200 Another case report indicated that a 41-year-old woman developed Kikuchi-Fujimoto disease (KFD) 201 after consuming MMS, which resulted in fever spiked to 40°C, chills, tachycardia, rigors, and dry cough.…”
Section: Unproven Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically this mechanism is evident in several case reports describing the toxic effects of chlorate exposure with patients exhibiting hemolysis, disseminated intravascular coagulation, liver failure, renal injury, and death. [18][19][20][21] Safety assessments have found the toxic dose of KClO 3 in humans to be 5 g and the lethal dose is estimated at 15 to 35 g. 22 To reach the toxic dose of 5 g of KClO 3 , ∼400 unburned matches must be consumed. 9,23 Toxicity data for children are scarce, with only 1 case report describing an infant death after the ingestion of 1 g of KClO 3 .…”
Section: Figurementioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD) converts MB to leucomethylene blue (LMB) and can act as activator of reductase enzymes (5). Although MB is an effective antidote to methemoglobinemia due to its reductase activity, it can be an oxidative agent in high doses by producing hydrogen peroxide and also can induce methemoglobinemia and red blood cell hemolysis (4,6,7).…”
Section: Introductionmentioning
confidence: 99%